Peak Car Use and the Rise of Global Rail: Why this is happening and what it means for large and small cities - Newman, Peter; Kenworthy, Jeffrey; Glazebrook, G. (Scientific Research Publishing, 2013)
The 21st century promises some dramatic changes—some expected, others surprising. One of the more surprising changes is the dramatic peaking in car use and an associated increase in the world’s urban rail systems. This paper sets out what is happening with the growth of rail, especially in the traditional car dependent cities of the US and Australia, and why this is happening, particularly its relationship to car use declines. It provides new data on the plateau in the speed of urban car transportation that supports rail’s increasing role compared to cars in cities everywhere, as well as other structural, economic and cultural changes that indicate a move away from car dependent urbanism. The paper suggests that the rise of urban rail is a contributing factor in peak car use through the relative reduction in speed of traffic compared to transit, especially rail, as well as the growing value of dense, knowledge-based centers that depend on rail access for their viability and cultural attraction. Finally, the paper suggests what can be done to make rail work better based on some best practice trends in large cities and small car dependent cities.